The effects of vitamin D treatment on the pain and the quality of life in elderly women [Yaşli kadinlarda D vitamini tedavisinin aǧri ve yaşam kalitesi üzerine etkileri] - (:unkn) unknown (My University, 2010)
Aim: Vitamin D synthesis in the body is reduced by older ages. It is known that in this age group with occurrence of vitamin D deficiency there is an increase in the number of muscle weakness, musculoskeletal system pain, balance impairment and falling. Quality of life is also negatively affected because of these problems. The aim of the present is to evaluate the effects of vitamin D treatment on pain and quality of life. Material and Methods: Fifty six patients over 65 years old with established vitamin D deficiency (<50 nmol/l) were enrolled in the study. 23 patients were given alphacalcidol 1 mg and elementary calcium 500 mg a day and the control group received elementary calcium 500 mg a day. All the patients were evaluated by visual analog scala (VAS), beck depression scale (BDS) and Short Form-36 (SF-36) at the starting of the treatment and at the end of 3rd and 6th months. Results: Pain relief started at 3rd month and continued till 6th month with vitamin D treatment (p<0.01) as pain increased in the calcium group. A marked decrease in the pain examination of SF-36 questionnaire and a significant increase in the social function subgroup (p<0.05) were found. No statistically significant between-group difference was found in Beck depression scala evaluation (p>0.05). Conclusion: It is observed that with alphacalcidol treatment the pain is reduced and thus the adaptation of the patients to social life is increased.
Keywords: Pain; Quality of life; Vitamin D